Students’ Perception of English Song as Media for Learning English Vocabulary at Junior High School - Annisa Devianti Ningrum (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research investigates the perceptions of junior high school students toward the use of English songs as media for learning English vocabulary. Vocabulary is one of the essential components in learning English and serves as a foundation for mastering four language skills: listening, speaking, reading, and writing. However, many students face difficulties in learning vocabulary due to lack of exposure, limited practice, and monotonous learning methods. Therefore, this study explores whether English songs, as an alternative and enjoyable medium, can enhance students’ interest and vocabulary acquisition. The study employed a descriptive qualitative method and involved three students from grade 8 at SMPN 4 Tanggul as participants. Data were collected through semi-structured interviews and analyzed using thematic analysis (Braun & Clarke, 2006). The criteria for participants included students who had been involved in learning vocabulary through songs and were willing to share their experiences and perceptions.
Entry oleh Arif 2026 Maret 05
Keywords: English Song as Media for Learning English; Students